HUBUNGAN PENDIDIKAN DAN LAMA KERJA BIDAN DENGAN PELAKSANAAN KOMUNIKASI TERAPEUTIK DI PUSKESMAS BASUKI RAHMAT KOTA BENGKULU - nuril ab sari (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2020)
ABSTRACT  In the midwifery care process it cannot be separated from communication, communication is a process of relationship between patient midwives and other health workers. This study aims to study the Relationship of Education and Length of Work with the Implementation of Therapeutic Communication in Puskesmas Basuki Rahmat, Bengkulu City. This research is a quantitative study, the population has the same opportunity to be selected as a sample that will be used. The size of the sample in this study is a sampling technique using Total Sampling where sampling is done as a whole where the entire population will be used as a sample as respondents ie 29 midwives . The sampling technique in this study uses total sampling where the overall sampling is done. Data collection in this study using a questionnaire. Research results Of 29 14 midwives whose implementation of therapeutic communication was poor and 15 midwives whose implementation of therapeutic communication was good. Of the 29 midwives there were 18 midwives with DIII education and 11 who had DIV / SI midwife education. Of the 29 midwives, there were 12 midwives 'long duration of work <3 years and there were 17 midwives' ≥ 3 years. There is an educational relationship with the implementation of therapeutic communication in the Basuki Rahmat Health Center in Bengkulu City with a moderate relationship category. There is a long working relationship with the implementation of therapeutic communication at the Basuki Rahmat Health Center in Bengkulu City with a moderate relationship category. Researchers suggest that midwives can engage in therapeutic communication so they can better serve patients and midwives can continue their education to improve the quality of the midwife Keywords:     Education, Duration of Work, Implementation of Therapeutic Communication